2021
DOI: 10.1007/s11783-021-1442-2
|View full text |Cite
|
Sign up to set email alerts
|

What have we known so far for fluorescence staining and quantification of microplastics: A tutorial review

Abstract: Understanding the fate and toxicity of microplastics (MPs, < 5 mm plastic particles) is limited by quantification methods. This paper summarizes the methods in use and presents new ones. First, sampling and pretreatment processes of MPs, including sample collection, digestion, density separation, and quality control are reviewed. Then the promising and convenient staining procedures and quantification methods for MPs using fluorescence dyes are reviewed. The factors that influence the staining of MPs, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Hydrophobic dyes, such as Nile Red (NR), preferentially combine with polymer materials with a lower polarity that are common in microplastics. 93 Prior research has shown that lipophilic dyes are effective in the quantification of small particles because of their high hydrophobicity. 94 NR (C 20 H 18 N 2 O 2 ; MW: 318.37) does not pose health hazards.…”
Section: Activity Three: Fluorescing Microplastics In Water Samplesmentioning
confidence: 99%
“…Hydrophobic dyes, such as Nile Red (NR), preferentially combine with polymer materials with a lower polarity that are common in microplastics. 93 Prior research has shown that lipophilic dyes are effective in the quantification of small particles because of their high hydrophobicity. 94 NR (C 20 H 18 N 2 O 2 ; MW: 318.37) does not pose health hazards.…”
Section: Activity Three: Fluorescing Microplastics In Water Samplesmentioning
confidence: 99%
“…The results are given in item concentrations [3]. Often only a few selected particles are analyzed [6,7]. However, this is not sufficient, particularly because -even with accurate sample preparation and mitigation of contamination -there are usually numerous non-plastic particles on a filter.…”
Section: Introductionmentioning
confidence: 99%
“…The most common polyethylene (PE) exhibits four typical bands between 1000 and cm − 1 in Raman spectra (1439 cm − 1 , 1295 cm − 1 , 1129 cm − 1 , cm − 1 ), whereas characteristic FTIR peaks (for instance due to the asymmetric and symmetric stretching of -CH 3 group) can be observed at: ~2915-2918 cm − 1 , ~2845-2850 cm − 1 , ~1463-1469 cm − 1 , ~713-720 cm − 1 . Other used methods include gas chromatography, mass spectrometry, and fluorescent staining (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%